Analisis Penerapan Service Marketing pada Bisnis Cuci Sepatu Erafftel - Gymnastiar Mustaqiim; Ihsan Hamdan; Taufik Arrahman (MASMAN Master Manajemen, 2026)
The development of the service sector in Indonesia requires micro-enterprises to adopt marketing strategies that enhance service quality and strengthen business competitiveness. In the context of service-based businesses, the service marketing approach is considered relevant as it emphasizes the management of service delivery and overall customer experience. This study aims to analyze the implementation of service marketing in Erafftel, a shoe cleaning service business located in Padang City, West Sumatra. The study employs a qualitative approach, with data collected through direct observation of operational activities and in-depth interviews with the business owner to obtain comprehensive information regarding service processes, service marketing strategies, and operational practices. The findings indicate that the services provided by Erafftel reflect the main characteristics of services, namely intangibility, inseparability, variability, and perishability. Furthermore, the service marketing mix consisting of seven elements—product, price, place, promotion, people, process, and physical evidence—has been implemented, although in a relatively simple and not yet fully structured manner. The people and process elements emerge as the most dominant factors influencing perceived service quality, as they are directly related to interactions between service providers and customers, while physical evidence serves as a supporting factor in building customer trust. The implications of this study suggest that strengthening the application of service marketing can contribute to improved service quality, increased customer satisfaction, and the long-term sustainability of micro service enterprises.